Prognostic implications of calculated Apo‐lipoprotein B in patients with ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: Outcome is tied to lower cut‐points. Issue 6 (4th May 2021) - Ghodsi, Saeed; Mohebi, Mehrnaz; Sadre‐Bafghi, Seyed‐Ali; Poorhosseini, Hamidreza; Salarifar, Mojtaba; Alidoosti, Mohammad; Haji‐Zeinali, Ali‐Mohammad; Amirzadegan, Alireza; Aghajani, Hassan; Jenab, Yaser; Hosseini, Zahra
Abstract: Background: Debates still surround using lipoproteins including Apo‐B in risk assessment, management, and prognosis of patients with coronary artery disease. During an acute ST‐segment elevation myocardial infarction, Apo‐B might help to achieve incremental prognostic information. Objective: We sought to determine the potential prognostic utility of calculated Apo‐B in a cohort of patients with STEMI undergoing primary PCI. Methods: A retrospective cohort study was conducted enrolling 2, 259 patients with a diagnosis of acute STEMI who underwent primary PCI. Apo‐B was obtained using a valid equation based on initial lipid measurements. High Apo‐B was defined as a level of 65 or higher. Primary endpoint of the study was major adverse cardiovascular events (MACE). Results: Mean age of the participants was 59.54 years and 77.9% of them were male. After a Median follow up of 15 (6.2) months, high Apo‐B was associated with MACE and the OR (95% CI) was 3.02 (1.07–8.47), p = .036. Odds ratios for prediction of MACE pertaining to LVEF, and smoking were 0.97 (p = .044), and 1.07 (p = .033), respectively. However, High Apo‐B was not able to predict suboptimal TIMI flow. Accordingly, the Odds ratio was 0.56 (0.17–1.87), p = 0.349. The power of High LDL‐C and Non‐HDLC for prediction of MACE were assessed in distinct models. Attained odds ratios were [2.40 (0.90–6.36), p = .077] and [1.80 (0.75–4.35), p = 0.191], respectively. Conclusion: Calculated Apo‐B appears to be a simple tool applicable for prediction of cardiovascular events in patients with STEMI superior to both Non‐HDLC and LDL‐C.